2008
DOI: 10.1037/0735-7044.122.1.224
|View full text |Cite
|
Sign up to set email alerts
|

Orbital spaceflight during pregnancy shapes function of mammalian vestibular system.

Abstract: Pregnant rats were flown on the NASA Space Shuttle during the early developmental period of their fetuses' vestibular apparatus and onset of vestibular function. The authors report that prenatal spaceflight exposure shapes vestibular-mediated behavior and central morphology. Postflight testing revealed (a) delayed onset of body righting responses, (b) cardiac deceleration (bradycardia) to 70°h ead-up roll, (c) decreased branching of gravistatic afferent axons, but (d) no change in branching of angular accelera… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
61
0

Year Published

2009
2009
2020
2020

Publication Types

Select...
4
2
1

Relationship

1
6

Authors

Journals

citations
Cited by 59 publications
(65 citation statements)
references
References 35 publications
2
61
0
Order By: Relevance
“…Later in evolution, the semicircular canals developed, enabling the detection of angular acceleration as well (Spoor et al, 1994(Spoor et al, , 2002. The vestibular system develops early in embryogenesis (Baker, 1998) so that it detects self-motion and gravitational vertical in the womb (Ronca et al, 2008); at the time of birth, it is almost fully functional, unlike the visual system, which undergoes a more substantial critical period after birth (Curthoys, 1983;Baker, 1998;Lai and Chan, 2001;Hooks and Chen, 2007). Because of its evolutionary significance, the vestibular system may provide the primary, baseline sensory information about self-motion against which all other sensory information is compared (Smith, 1997;Borel et al, 2008).…”
Section: Why Should Manipulation Of the Vestibular System Have Effectmentioning
confidence: 99%
“…Later in evolution, the semicircular canals developed, enabling the detection of angular acceleration as well (Spoor et al, 1994(Spoor et al, , 2002. The vestibular system develops early in embryogenesis (Baker, 1998) so that it detects self-motion and gravitational vertical in the womb (Ronca et al, 2008); at the time of birth, it is almost fully functional, unlike the visual system, which undergoes a more substantial critical period after birth (Curthoys, 1983;Baker, 1998;Lai and Chan, 2001;Hooks and Chen, 2007). Because of its evolutionary significance, the vestibular system may provide the primary, baseline sensory information about self-motion against which all other sensory information is compared (Smith, 1997;Borel et al, 2008).…”
Section: Why Should Manipulation Of the Vestibular System Have Effectmentioning
confidence: 99%
“…The numbers of synapses per 18.06 μm 2 were 39.6 ± 13.5 (mean ± SD) in the G1g and 43.5 ± 18.5 in the F0g embryos. The same DiI tracer technique applied to the posterior canal organ revealed no difference in the projection pattern of this organ between F0g and G1g embryos (Bruce and Fritzsch, 1997;Ronca et al, 2008). Neurons within the vestibular nuclei of rats FIGURE 16.10 Redistribution of synaptophysin in vestibular type I hair cells from the utriculus of 2g reared rats at day of birth (P0) and 6th post-natal day (P6) and from the crista lateralis from P6 rats compared to 1g reared rats.…”
Section: Central Nervous System: the Vestibular Nucleimentioning
confidence: 96%
“…Physiological activity of afferents matures during the first three postnatal weeks. Connections with the cerebellum, which is part of the control mechanisms of vestibulo-ocular and vestibulospinal reflexes, develop between the first and fourth post-natal week (Lannou et al, 1983;Ronca and Alberts, 2000;Ronca 2003;Raymond et al, 2003;Ronca et al, 2008).…”
Section: Studies In Higher Vertebratesmentioning
confidence: 99%
See 1 more Smart Citation
“…Following 11 days in space during the prenatal period (μG, E9-E20), vestibular-specific tests performed on rats suggested they had a retarded ability to respond to gravistatic stimuli (Ronca and Alberts, 1997), abnormal water immersion responses , and increased bradycardia following roll stimulation (Ronca et al, 2008). The labeling of vestibular projections revealed that development in space might decrease the number of gravistatic-afferent synapses to the medial vestibular nucleus but would not change the overall amount of connections, suggesting a trade-off in favor of canal afferent synapses (Ronca et al, 2008). Current evidence suggests that in these animals, adaptation to normal gravity can occur in a few weeks after returning to earth.…”
Section: Weightlessness Experiments In Rodentsmentioning
confidence: 99%